A Case Report of COVID-19 in Yemen: Detailed Clinical Observations - Alakhali, Khaled M.; Alshahrani, Sultan M.; Al-Worafi, Yaser Mohammed; Irawati, Lyna (Sciencedomain International, 2020)
Coronavirus (COVID-19) is an infectious disease caused by a newly discovered coronavirus. We reported a 59-year-old Yemeni physician who was treated at home with complaints of COVID-19 symptoms. After receiving the treatment according to the COVID-19 guidelines established in Yemen, the patient made a slow recovery from 8 May 2020 to 28 May 2020. In conclusion, COVID-19 has a complicated clinical course and poor prognosis. Nevertheless, early aggressive treatment with an appropriate protocol could improve patient outcomes. However, in COVID-19, the thyroid gland plays a role in the immune system and medical professionals should consider assessing the thyroid gland in COVID-19 cases.